PERBANDINGAN HASIL BELAJAR MATEMATIKA SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF STRUKTURAL NHT DAN MODEL PEMBELAJARAN EKSPOSITORI - Heryanto Heryanto (Universitas Quality, 2018)
The study was conducted with the aim to know which higher mathematics learningoutcomes of students were taught using NHT structural cooperative learning model rather thanusing an expository learning model. The location of research in SMA Negeri 1 Simpang EmpatKaro Regency with population of all students of class X and sample taken two classes withcluster random sampling technique which each class consists of 35 students. Data analysistechnique used is t-test with significance level ( )= 0,05.The results showed that (1) the average of mathematics learning outcomes of students who weretaught using NHT structural cooperative learning model was obtained 27,57; (2) the average ofmathematics learning result of students taught using expository learning model is 25,03; and (3)the mathematics learning outcomes of students taught using NHT structural cooperativelearning model is higher than using the expository learning model.